EFEKTIVITAS VAKSIN TY21A ORAL DIBANDINGKAN DENGAN VAKSIN PARENTERAL DALAM PENCEGAHAN TRANSMISI DEMAM TIFOID BAGI WISATAWAN - Amelia Manatar; Reynaldi Hadiwijaya (Intisari Sains Medis, 2014)
International travel, including travelling to poor and developing country has increased. More than 900 million people travel internationally each year. The risk of infection while travelling varies widely, depending on the closeness of relationship, length of exposure, and nature of the contact. Typhoid fever is one of many health problems for travelers in developing country, because it can increase the morbidity and mortality rate. Thatâ€™s why it takes a precautionary measure to reduce the incidence of typhoid fever especially for travelers. The current preventive intervention for typhoid fever is vaccination. There are twoÂ kinds of vaccines that are widely used, such as parenteral vaccine and oral Ty21a vaccine. These vaccines have it's own up and downside. That's why we have to find out which vaccine is better to prevent the transmission of typhoid fever, especially for high risk traveler.